Collaborative AI in Music Composition: Human-AI Symbiosis in Creative Processes - Sunish Vengathattil (International Journal of Management Science and Information Technology, 2025)
Artificial Intelligence (AI) has ushered in a revolutionary change that mixes creative abilities between human composers and computer-powered intelligence during musical composition. The investigation examines the musical application of collaborative AI which exists as an aid to composers by suggesting ideas and creating motifs alongside enhancing musical arrangements. OpenAI’s MuseNet alongside Google’s MusicLM brought about new generative model technologies which enable musicians to have real-time access to adaptive tools that interpret as well as transform musical concepts. Based on secondary research and case studies, the article examines human composer-AI system partnerships to explain how their combined work restructures artistic authorship and creative methods. The paper uses today's artists with AI support and collaborative works between different fields to demonstrate the partnership's core dynamics. The discussion explores two main elements about AI music production which are human involvement versus programming automation alongside understanding emotional integrity in synthetic musical compositions together with co-creative copyrights regulations. This research evaluates how partnership between humans and AI components transforms musical education along with the process of composition for those without a musical background while testing established artistic boundaries of genre classification and original content production. This research project depicts AI as an amplification force that generates human creativity rather than being considered disruptive by showing how intelligent feedback systems work together with human agents. Co-creation behavior in this hybrid method motivates a fresh depiction of musical expression which sparks explorations about art creation and authorship roles and identity function in the future.